The Islamic roots of democratic pluralism - Sachedina, Abdulaziz Abdulhussein, 1942- (Oxford University Press, 2001)
This book tackles the most significant issues facing Muslims today. Sachedina argues that we must reopen the doors of religious interpretation--to correct false interpretations, replace outdated laws, and formulate new doctrines. His book critically analyzes Muslim teachings on such issues as pluralism, civil society, war and peace, and violence and self-sacrifice.